The extraterritorial quest for justice: the case for imposing a "duty of care" on parent companies in the absence of a binding business and human rights treaty - Naidoo, Priyanka (Centre for Law and Society, 2025)
In an increasingly globalised world, Multi-National Corporations (MNCs) have become as influential as some States. Concerningly, States no longer have a monopoly over human rights violations, nor are they seen to be the primary duty-bearers. Despite this, there are no effective accountability mechanisms to hold MNCs liable in the international sphere. This often leaves victims of human rights violations without recourse or forced to seek justice in other jurisdictions. Against the backdrop of the international negotiations for a binding business and human rights treaty, courts have been willing to impose a ‘duty of care' on parent companies for the acts or omissions carried out by their subsidiaries abroad. This has forced claimants to overcome numerous procedural hurdles when attempting to access justice. In particular, extra-territoriality has been the biggest barrier for foreign claimants who have attempted to sue the parent companies in their domiciled State. This minor dissertation will explore the imposition of the notion of a parent company's ‘duty of care' towards their subsidiaries for harm committed extra-territorially. In doing so, it will look at the changing understanding of corporations in our society and the need for greater access to justice. This dissertation draws on the United Kingdom Supreme Court ruling in Vedanta v Lungowe and discusses how the landmark ruling will impact future cases of this nature and in particular The Kabwe class action before the Johannesburg High Court in South Africa. The question that this dissertation seeks to address is “how can the imposition of a ‘duty of care' on a parent company for harms caused by their subsidiaries abroad improve corporate accountability in the absence of a binding business and human rights treaty”.